Turbo Design as a Countermeasure for Traffic Safety and Operation at Roundabouts - Noor Jabbar Jihad; Ewadh, Hussein Ali; Almuhanna, Raid R.A. (Journal of Engineering and Sustainable Development, 2026)
Turbo roundabouts have recently been developed in various nations due to their numerous benefits. The paper assesses the safety and efficiency of turbo roundabouts. Replacement is done without damaging private property. Evaluations are performed by using two simulations. VISSIM is used to evaluate operational performance by identifying delays and service levels. SSAM 3.0 evaluates safety performance by identifying two conflict-severity indexes: the time-to-collision (TTC) and post-encroachment time (PET). Turbo roundabouts improve the level of service (LOS) compared to multi-lane ones. In the Al-Mohafda roundabout, LOS is changed from LOS F to LOS D, reducing vehicle delays by 66%. In addition, Al-Tarbia and Said Al-Assar roundabouts (LOS) changed from (LOS F) to (LOS E), reducing vehicle delays by 55% and 63%, respectively. Turbo roundabouts have superior traffic operating safety. TTC increased by 41% at the Al Mohafada and Al-Tarbia roundabouts, which are classified as high-risk to medium-risk roundabouts, and increased by 33% at the Said Al-Assar roundabouts. The total number of conflicts decreased by 69%, 74%, and 85% at the three roundabouts (Al-Tarbia, Saeed Al Asar, and Al Mohafada), respectively. Legislators may thoroughly study proposed legislation and work towards integrating turbo roundabouts as a potential solution for intersections.